Advances in the gene therapy of monogenic blood cell diseases. Issue 1 (11th July 2019) - Bueren, Juan A.; Quintana‐Bustamante, Oscar; Almarza, Elena; Navarro, Susana; Río, Paula; Segovia, José C.; Guenechea, Guillermo
Abstract: Hematopoietic gene therapy has markedly progressed during the last 15 years both in terms of safety and efficacy. While a number of serious adverse events (SAE) were initially generated as a consequence of genotoxic insertions of gamma‐retroviral vectors in the cell genome, no SAEs and excellent outcomes have been reported in patients infused with autologous hematopoietic stem cells (HSCs) transduced with self‐inactivated lentiviral and gammaretroviral vectors. Advances in the field of HSC gene therapy have extended the number of monogenic diseases that can be treated with these approaches. Nowadays, evidence of clinical efficacy has been shown not only in primary immunodeficiencies, but also in other hematopoietic diseases, including beta‐thalassemia and sickle cell anemia. In addition to the rapid progression of non‐targeted gene therapies in the clinic, new approaches based on gene editing have been developed thanks to the discovery of designed nucleases and improved non‐integrative vectors, which have markedly increased the efficacy and specificity of gene targeting to levels compatible with its clinical application. Based on advances achieved in the field of gene therapy, it can be envisaged that these therapies will soon be part of the therapeutic approaches used to treat life‐threatening diseases of the hematopoietic system. Abstract :